Efficacy and tolerability of peptide receptor radionuclide therapy (PRRT) in advanced metastatic bronchial neuroendocrine tumours (NETs). (December 2020) - Mirvis, Eitan; Toumpanakis, Christos; Mandair, Dalvinder; Gnanasegaran, Gopinath; Caplin, Martyn; Navalkissoor, Shaunak
Highlights: PRRT is an effective treatment in bronchial neuroendocrine tumours. PRRT can be effective even in heavily pre-treated patients. PRRT is safe in bronchial neuroendocrine tumours. Abstract: Introduction: Peptide receptor radionuclide therapy (PRRT) has been proven to be effective in gastro-entero-pancreatic neuroendocrine tumours (NETs) using 90 Yttrium ( 90 Y)- or 177 Lutetium ( 177 Lu)-based somatostatin peptides, with 177 Lu-DOTATATE recently licensed. There is less published evidence of PRRT in metastatic bronchial NETs. Objective: The aim of this study was to evaluate the efficacy, safety and toxicity of PRRT in patients with bronchial NETs, to expand the evidence base in this rare type of tumour. Materials and methods: This was a retrospective analysis of all patients with moderate to well-differentiated typical or atypical bronchial NETs treated at the Royal Free Hospital Nuclear Medicine Department with at least two cycles of 90 Y-DOTA−OCTREOTATE and/or 177 Lu-DOTA−OCTREOTATE between 2009 and 2020. Response rates, progression free survival (PFS), overall survival and toxicity were evaluated. Factors associated with treatment response were evaluated. Results: Of the 25 patients with bronchial NETs treated with PRRT in our department between 2009–2020, 7 (28 %) had 90 Y-DOTATATE and 18 (72 %) had 177 Lu-DOTATATE. 44 % of patients had PRRT as third, fourth of fifth line treatment. 72 % of patients had liver metastases and 76 % skeletal metastases at baseline. Median progression-free survival (PFS) was 17 months ( 177 Lu-DOTATATE = 18 months; 90 Y-DOTATATE = 12 months) and the median overall survival was 42 months. High proliferation rate (ki-67 > 20) and low somatostatin receptor (SSR) uptake (score of 2) were associated with shorter PFS. Conclusion: PRRT appears to be a safe treatment in somatostatin receptor positive bronchial NETs, even in patients who have been heavily pre-treated. The efficacy of PRRT is comparable with if not favourable to other systemic therapeutic options.